Sampled-data H∞ filtering for Markovian jump singularly perturbed systems with time-varying delay and missing measurements. Issue 3 (17th February 2018) - Yan, Yifang; Yang, Chunyu; Ma, Xiaoping; Zhou, Linna
ABSTRACT: In this paper, sampled-data H ∞ filtering problem is considered for Markovian jump singularly perturbed systems with time-varying delay and missing measurements. The sampled-data system is represented by a time-delay system, and the missing measurement phenomenon is described by an independent Bernoulli random process. By constructing an ϵ-dependent stochastic Lyapunov–Krasovskii functional, delay-dependent sufficient conditions are derived such that the filter error system satisfies the prescribed H ∞ performance for all possible missing measurements. Then, an H ∞ filter design method is proposed in terms of linear matrix inequalities. Finally, numerical examples are given to illustrate the feasibility and advantages of the obtained results.